Learning from research and development projects / the role of post-project reviews - Koners, Ursula (Cranfield University, 2005)
Successful innovation depends to a high degree on an organization’s ability to develop an effective Research & Development (R&D) process and during the last decades many companies have adopted Stage-Gate® or similar methodologies. Although such methodologies are credited with significantly improving R&D results at many companies, there is still potential for improvement, if organizations can learn from projects. Each and every R&D project should not only result in a successful new product but also generate learning for the organization, because this has a high importance for the competitive advantage of an organization. Post-project reviews (PPRs) are recognized by both practitioners and academics as an appropriate mechanism to stimulate project-to-project learning in R&D project teams. However, PPRs are used by relatively few companies, and those that do utilize them often fail to do so adequately. Surprisingly, although PPRs are widely perceived to be a useful tool, empirical research on how they can best be used and how they support learning within a project team is very limited. This thesis addresses this gap in the extant knowledge and describes five in-depth exploratory case studies, which investigated how PPRs are conducted, how they are perceived by R&D managers and the project-to-project learning that can result from PPRs. Based on a complex research design which combines qualitative and quantitative data from documents, interviews and the observation of PPR meetings, the results show that current PPR practices vary much across different organizations. Furthermore, R&D managers perceive PPRs as important for learning in R&D project teams but difficult to manage effectively. An important result was also that tacit knowledge and experiences play an important role when analysing project-to-project learning. Although the operationalization of tacit knowledge is difficult, the detailed analysis of lessons learnt and metaphors used allowed to gather conclusions on the supporting role of PPRs for the creation and transfer of both explicit and tacit knowledge.